Learn more about

Refine search

Results (displaying matches 1-50 of 6879) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
360.a.6480.1 360.a \(y^2 + (x^3 + x)y = -3x^4 + 7x^2 - 5\) $G_{3,3}$ 0
600.a.18000.1 600.a \(y^2 + xy = 10x^5 - 18x^4 + 8x^3 + x^2 - x\) $G_{3,3}$ 0
600.b.450000.1 600.b \(y^2 + (x^3 + x)y = -5x^4 + 25x^2 - 45\) $G_{3,3}$ 0
630.a.34020.1 630.a \(y^2 + (x^2 + x)y = 3x^5 + 10x^4 - 23x^2 - 6x + 15\) $G_{3,3}$ 0
708.a.181248.1 708.a \(y^2 + (x^3 + 1)y = -x^6 - 4x^5 + 9x^4 + 48x^3 - 41x^2 - 98x - 36\) $\mathrm{USp}(4)$ 0
816.a.39168.1 816.a \(y^2 + (x^2 + 1)y = 3x^5 - 4x^3 - x^2 + x\) $\mathrm{USp}(4)$ 0
936.a.1872.1 936.a \(y^2 + (x^3 + x)y = -x^6 - 9x^4 - 32x^2 - 39\) $G_{3,3}$ 0
1050.a.131250.1 1050.a \(y^2 + (x^2 + x)y = 3x^6 + 8x^5 + 15x^4 + 17x^3 + 15x^2 + 8x + 3\) $G_{3,3}$ 0
1344.a.4032.1 1344.a \(y^2 + xy = -x^6 - 12x^4 - 48x^2 - 63\) $N(G_{1,3})$ 0
1470.a.2940.1 1470.a \(y^2 + (x^2 + x)y = -x^6 + 2x^5 - 5x^4 + 4x^3 - 5x^2 + 2x - 1\) $G_{3,3}$ 0
1575.a.23625.1 1575.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 6x^3 + 2x^2 + 7x - 4\) $\mathrm{USp}(4)$ 1
1575.a.165375.1 1575.a \(y^2 + (x^2 + x + 1)y = -x^5 + 2x^4 + x^2 - 2x\) $\mathrm{USp}(4)$ 1
1584.a.684288.1 1584.a \(y^2 + (x^3 + x)y = -x^6 + 6x^4 - 17x^2 + 11\) $G_{3,3}$ 0
1680.a.16800.1 1680.a \(y^2 + (x^3 + x)y = -x^6 - 18x^4 - 136x^2 - 350\) $G_{3,3}$ 0
1920.a.368640.1 1920.a \(y^2 + (x^3 + x^2 + x + 1)y = 5x^6 + 6x^5 + 17x^4 + 12x^3 + 17x^2 + 6x + 5\) $G_{3,3}$ 0
1935.a.52245.2 1935.a \(y^2 + xy = x^5 - 2x^4 - 82x^3 - 20x^2 + 927x - 1134\) $\mathrm{USp}(4)$ 0
2058.a.2058.1 2058.a \(y^2 + (x^3 + 1)y = 5x^6 - 4x^5 - 5x^4 + 14x^3 - 5x^2 - 4x + 5\) $N(G_{1,3})$ 0
2169.a.175689.1 2169.a \(y^2 + (x^2 + x)y = x^5 - 9x^4 + 22x^3 - 14x^2 - x\) $N(G_{3,3})$ 0
2304.a.13824.2 2304.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^3 + 3x^2 + x + 2\) $\mathrm{USp}(4)$ 1
2304.a.13824.1 2304.a \(y^2 + y = 2x^5 + 3x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2457.a.95823.1 2457.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 3x^3 + 6x^2 - 6x + 2\) $\mathrm{USp}(4)$ 1
2457.a.154791.1 2457.a \(y^2 + (x^3 + 1)y = x^5 - 3x^3 - x^2 + 2\) $\mathrm{USp}(4)$ 1
2457.b.199017.1 2457.b \(y^2 + (x^2 + x)y = -x^5 + 4x^4 + x^3 - 13x^2 - 9x\) $N(G_{3,3})$ 0
2560.a.5120.1 2560.a \(y^2 = x^5 - x^4 - 2x^3 + x^2 + x\) $N(G_{3,3})$ 0
2560.a.819200.1 2560.a \(y^2 = 2x^5 - 7x^4 + 2x^3 + 7x^2 + 2x\) $N(G_{3,3})$ 0
2600.a.338000.1 2600.a \(y^2 + xy = 10x^5 + 8x^4 - 5x^3 - 3x^2 + x\) $\mathrm{USp}(4)$ 0
2640.a.2640.1 2640.a \(y^2 + (x^3 + x)y = -x^6 - 10x^4 - 40x^2 - 55\) $G_{3,3}$ 0
2688.a.172032.1 2688.a \(y^2 + y = -12x^6 - 36x^5 - 61x^4 - 62x^3 - 42x^2 - 17x - 4\) $G_{3,3}$ 0
2739.a.2739.1 2739.a \(y^2 + (x^2 + x + 1)y = 3x^6 + 26x^5 + 40x^4 + 25x^3 + 22x^2 + 7x - 8\) $\mathrm{USp}(4)$ 0
2745.a.502335.1 2745.a \(y^2 + (x^2 + x)y = 3x^5 + 7x^4 + 5x^3 - x\) $\mathrm{USp}(4)$ 0
2808.b.454896.1 2808.b \(y^2 + (x^3 + x)y = -9x^4 + 95x^2 - 351\) $G_{3,3}$ 1
2872.a.367616.1 2872.a \(y^2 + xy = -8x^6 - 28x^5 - 65x^4 - 88x^3 - 88x^2 - 51x - 20\) $\mathrm{USp}(4)$ 1
2880.e.43200.1 2880.e \(y^2 + xy = 3x^6 + 38x^4 + 160x^2 + 225\) $G_{3,3}$ 1
2898.a.8694.1 2898.a \(y^2 + (x^3 + 1)y = -10x^6 + 18x^5 - 23x^4 + 36x^3 - 23x^2 + 18x - 10\) $G_{3,3}$ 0
2976.a.761856.1 2976.a \(y^2 + y = -4x^6 - 20x^5 - 19x^4 + 18x^3 + 5x^2 - 3x - 1\) $\mathrm{USp}(4)$ 0
3003.b.819819.1 3003.b \(y^2 + (x^2 + 1)y = x^5 + 4x^4 + 3x^3 + x\) $\mathrm{USp}(4)$ 1
3030.a.90900.1 3030.a \(y^2 + xy = 5x^5 + 28x^4 + 52x^3 + 33x^2 + 2x\) $\mathrm{USp}(4)$ 1
3072.b.196608.2 3072.b \(y^2 = 2x^6 + 9x^4 + 13x^2 + 6\) $N(G_{1,3})$ 0
3080.a.67760.1 3080.a \(y^2 + (x + 1)y = 2x^5 - 2x^4 - x^2\) $\mathrm{USp}(4)$ 1
3120.b.199680.1 3120.b \(y^2 + xy = -80x^6 - 189x^4 - 149x^2 - 39\) $G_{3,3}$ 0
3150.b.78750.1 3150.b \(y^2 + (x^3 + 1)y = -4x^4 + 5x^3 + 14x^2 - 39x + 26\) $G_{3,3}$ 1
3168.a.684288.1 3168.a \(y^2 + (x^3 + x)y = -x^6 - 7x^4 - 17x^2 - 11\) $G_{3,3}$ 0
3200.f.819200.1 3200.f \(y^2 = x^6 - 5x^4 + 7x^2 - 2\) $G_{3,3}$ 1
3219.a.280053.1 3219.a \(y^2 + (x^3 + x^2)y = -3x^4 - 5x^3 + 6x^2 + 7x - 6\) $\mathrm{USp}(4)$ 1
3336.b.20016.1 3336.b \(y^2 + (x^2 + 1)y = x^5 - x^4 - x\) $\mathrm{USp}(4)$ 1
3360.b.241920.1 3360.b \(y^2 + (x^2 + 1)y = -135x^6 - 96x^4 - 23x^2 - 2\) $G_{3,3}$ 0
3417.a.686817.1 3417.a \(y^2 + (x^2 + x)y = 3x^5 - 9x^4 + 6x^3 - x\) $\mathrm{USp}(4)$ 0
3429.a.30861.1 3429.a \(y^2 + xy = x^5 + x^4 - 8x^3 - 9x^2 + 16x + 19\) $\mathrm{USp}(4)$ 1
3465.a.800415.1 3465.a \(y^2 + (x^3 + 1)y = x^5 - 4x^3 - 3x^2 + 3x + 2\) $\mathrm{USp}(4)$ 1
3515.a.333925.1 3515.a \(y^2 + (x^2 + 1)y = x^5 - 6x^3 + 2x^2 + 2x\) $\mathrm{USp}(4)$ 1
Next

Download all search results for